2018
DOI: 10.1097/md.0000000000013417
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effects of transforaminal and interlaminar percutaneous endoscopic discectomy for lumbar disc herniation

Abstract: The aim of this study is to observe the therapeutic effect of percutaneous endoscopic discectomy and its influencing factors for lumbar disc herniation and compare the advantages and disadvantages of transforaminal and interlaminar of percutaneous endoscopy.Data from 143 patients with lumbar disc herniation were respectively collected, including demographic and clinical data. Study population were divided into curative effect group and poor curative effect group, and logistic regression was used to explore the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 23 publications
2
28
0
2
Order By: Relevance
“…Previous research has shown that the preoperative status of some patients was a potential risk factor for poor outcome or recurrence [ 8 , 15 18 , 23 ]. Older age has been shown to be a risk factor for poor outcome or recurrence in many studies [ 7 , 15 , 18 , 23 , 28 ]. In the present study, older age was significantly associated with poorer surgical outcome but not with recurrence rate in univariable study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has shown that the preoperative status of some patients was a potential risk factor for poor outcome or recurrence [ 8 , 15 18 , 23 ]. Older age has been shown to be a risk factor for poor outcome or recurrence in many studies [ 7 , 15 , 18 , 23 , 28 ]. In the present study, older age was significantly associated with poorer surgical outcome but not with recurrence rate in univariable study.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have proven its benefits, including less blood loss, less wound pain, and shorter recovery time [2][3][4][5][6]. However, large studies discussing potential factors associated with poor surgical outcomes were few [7][8][9][10][11][12]. Some studies have identified factors, such as herniation type, patient comorbidity, and age, as potential causes of surgical failure or unfavorable outcomes in traditional open or microscopic surgery, but few studies have investigated factors of FELD associating poor outcomes [8,[13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…According to the approach, the percutaneous endoscopic lumbar discectomy is divided into the posterior approach and the lateral posterior approach [9,10], whereas the lateral posterior approach is divided into the Yeung endoscopic spine system (YESS) [11] and the transforaminal endoscopic spine system (TESSYS) [12,13]. Depending on the segment of disk herniation, the type of disk herniation, and individual surgical habits, the surgeon may perform the endoscopic surgery with different approaches [9,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, in MD, it is inevitable that the laminabony structure and the spine tension band will be destroyed, which may cause low back pain and lumbar instability after operation. [ 11 15 ] In the past few years, the percutaneous endoscopic discectomy (PED) has increasingly become a common treatment for the symptomatic lumbar disc herniation. In numerous former reports, it possesses a good therapeutic effect on lumbar disc herniation.…”
Section: Introductionmentioning
confidence: 99%